Malay-Muslim women machineries: PAS Dewan Muslimat and UMNO Wanita in GE14. Issue 2 (3rd March 2020) - Arosoaie, Aida
ABSTRACT: This article investigates the self-positioning and capacity for action of female members of UMNO and PAS, contributing to a deeper understanding of women's political activism in Malaysia in the 2018 General Elections. It engages a multidisciplinary conceptual framework which explains the possibility of agency within Islamic notions of self and society, along with the possibility of liberatory narratives in the absence of liberal and secular ontologies. Based on fieldwork and first-hand sources, the article argues that the unique self-positioning and capacity for action of UMNO's Wanita and PAS' Dewan Muslimat in relation to Islamic frameworks and the imperatives of Malay-Muslim empowerment agenda accomplish seemingly contradictory ends: being active contributors to their parties' success despite being in a subordinate position to their male peers, while also supporting women empowerment agendas and calling for greater female representation in politics.